Highly Efficient Genome Engineering in Bacillus anthracis and Bacillus cereus Using the CRISPR/Cas9 System - Wang, Yanchun; Wang, Dongshu; Wang, Xiaojing; Tao, Haoxia; Feng, Erling; Zhu, Li; Pan, Chao; Wang, Bowen; Liu, Chunjie; Liu, Xiankai; Wang, Hengliang (Frontiers in Microbiology, 2019)
Genome editing is an effective tool for the functional examination of bacterial genes and for live attenuated vaccine construction. Here, we report a method to edit the genomic DNA of Bacillus anthracis and Bacillus cereus using the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein (Cas)9 system. Using two prophages in B. anthracis as targets, large-fragment deletion mutants were achieved with rates of 100% or 20%. In B. cereus, we successfully introduced precise point mutations into plcR, with phenotypic assays showing that the resulting mutants lost hemolytic and phospholipase enzyme activities similar to B. anthracis, which is a natural plcR mutant. Our study indicates that CRISPR/Cas9 is a powerful genetic tool for genome editing in the Bacillus cereus group, and can efficiently modify target genes without the need for residual foreign DNA such as antibiotic selection markers. This system could be developed for use in the generation of marker-free live anthrax vaccines or for safer construction of microbiological candidate-based recombinant B. cereus.